Altered Responsiveness to TGFβ and BMP and Increased CD45+ Cell Presence in Mitral Valves Are Unique Features of Ischemic Mitral Regurgitation. Issue 6 (8th April 2021) - Castillero, Estibaliz; Howsmon, Daniel P.; Rego, Bruno V.; Keeney, Samuel J.; Driesbaugh, Kathryn H.; Kawashima, Takayuki; Xue, Yingfei; Camillo, Chiara; George, Isaac; Gorman, Robert C.; Gorman, Joseph H.; Sacks, Michael S.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Objective: Ischemic mitral regurgitation (IMR) often develops after an ischemic event, which results in distortion of the valvulo-ventricular complex and incomplete mitral valve (MV) leaflet coaptation. After left ventricular ischemic events, only some patients develop IMR. The susceptibility of the MV to remodel may influence whether IMR develops. We hypothesized that impaired signaling response in MV cells may contribute to IMR development by inducing maladaptive tissue remodeling. Approach and Results: Sheep (n=14) were subjected to ligation of the circumflex coronary artery to induce myocardial infarction. IMR was reported by echocardiography. MV leaflets and MV interstitial cells (MVICs) were collected at baseline (control, n=10), 4 and 8 weeks post-myocardial infarction. RNA sequencing highlighted differences in TGFβ (transforming growth factor beta) signaling between MV with/without IMR. SMAD6/7 and ID2 (inhibitor of DNA binding 2) were the highest increased TGFβ-signaling genes associated with IMR. MVICs from myocardial infarction sheep were less responsive to BMP (bone morphogenic protein) 4 pro-osteogenic stimulation (ID2, OPN [osteopontin], and OC [osteocalcin] mRNA) than control. MVICs from IMR sheep had a diminished COL (collagen) 1A1 mRNA response to TGFβ1 and enhanced prochondrogenic RUNX2 (runt-related transcription factor 2) and SOX9 mRNA response to BMP4 versus non-IMR MVICs. Baseline CD45 (cluster of differentiation) expression was detectable only in IMR MVICs. Upon TGFβ1 stimulation, CD45 expression was detected in all groups. Immunostaining confirmed increased presence of CD45+ cells in IMR MV interstitium. Conclusions: MVs from sheep with IMR had an altered TGFβ/BMP response, associated with increased CD45+ cell presence within the tissue interstitium. Pharmacological strategies aimed to modulate TGFβ/BMP signaling after myocardial infarction may protect from pathological MV remodeling leading to IMR.